Nematode behaviour - Gaugler, Randy; Bilgrami, Anwar L., 1956- (Cabi Publishing., 2004)
"In addition to specialists in nematology, the book will be of interest to those with backgrounds in behaviour, plant pathology, entomology, ecology, zoology, evolutionary biology and parasitology."--Jacket